2004
DOI: 10.1074/jbc.m314082200
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Kinase C Inhibitor Bisindolyl Maleimide 2 Binds with Reversed Orientations to Different Conformations of Protein Kinase A

Abstract: As the key mediators of eukaryotic signal transduction, the protein kinases often cause disease, and in particular cancer, when disregulated. Appropriately selective protein kinase inhibitors are sought after as research tools and as therapeutic drugs; several have already proven valuable in clinical use. The AGC subfamily protein kinase C (PKC) was identified early as a cause of cancer, leading to the discovery of a variety of PKC inhibitors. Despite its importance and early discovery, no crystal structure fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 46 publications
(41 reference statements)
4
44
0
Order By: Relevance
“…To elucidate the signaling mechanisms by which intracellular M. leprae induce MEK-independent Erk1͞2 activation, 30-dayinfected Schwann cells were serum-starved for 48 h with known inhibitors of major signaling pathways. We found that PKC paninhibitor (PKCI) bisindolyl maleimide-I (20 nM) (26), in the presence of MEKI and PI3KI, significantly blocked M. lepraeinduced phosphorylation of Erk1͞2 (Fig. 4A), suggesting a critical role of PKC in MEK-independent activation of Erk1͞2.…”
Section: Resultsmentioning
confidence: 94%
“…To elucidate the signaling mechanisms by which intracellular M. leprae induce MEK-independent Erk1͞2 activation, 30-dayinfected Schwann cells were serum-starved for 48 h with known inhibitors of major signaling pathways. We found that PKC paninhibitor (PKCI) bisindolyl maleimide-I (20 nM) (26), in the presence of MEKI and PI3KI, significantly blocked M. lepraeinduced phosphorylation of Erk1͞2 (Fig. 4A), suggesting a critical role of PKC in MEK-independent activation of Erk1͞2.…”
Section: Resultsmentioning
confidence: 94%
“…selectivity. 43 The residues that make up the binding site region in each of the kinases under consideration are indicated in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is visible in two of the PKAR5 complexes, and the question arises whether the peptide flip could be related to a specific mutation of PKAR5. Notably, we observed this phenomenon before in the PKA staurosporine complex (1STC) and in one of the two molecules in the asymmetric unit of a PKAB3 Bim2 complex (35).…”
Section: Effect Of the Mutations On Y-27632mentioning
confidence: 98%